Peningkatan keterampilan penggunaan alat praktikum dalam pembelajaran ipa menggunakan model problem based learning (PBL) pada peserta didik kelas V sekolah dasar - Niagati, Anggit; Atmojo, Idam Ragil Widianto; Sularmi, Sularmi (Universitas Sebelas Maret, 2020)
The purpose of this research is improving the skills to use practical tools in science learning by using the PBL model. This research is Classroom Action Research with three cycles. The subjects of the study were 34 students and grade 5 students at SD Negeri Pajang 4 in the 2019/2020 academic year. The technique in collecting data is observation and interviewand documentation with data analysis of content validity. The analysis of the data used is the interactive analysis. The initial conditions prior to action are the percentage of students on skills using tools according to the procedure of 3.03% and there are no students who are very skilled at the skills of arranging tools according to the series drawings. The first cycle resulting in a percentage of very skilled students using tools according to procedures 9.09% and arranging tools according to series drawings 24.24%. The second cycle resulting in a percentage of very skilled students using tools according to procedures 38.71% and arranging tools according to series drawings of 51.61%. The third cycle resulting in a percentage of very skilled students using the tools according to the procedure is the same as assembling the tools according to the series drawings that is 87.10%. Based on the result of the research, it can be conclude that the PBL learning model can improve the practice of using practical tools in natural science learning in grade V students of SD Negeri Pajang 4 in the 2019/2020 school year. Teachers can use the PBL model to improve their skills in using practical tools.